MENGEMBANGKAN PROSES KREATIF, ORIGINALITAS, DAN KOMUNIKASI DALAM PERIKLANAN - Lia Kurniawati; Milla Mustikawati Sugandi; Agnia Nurul Huda (JURNAL ILMIAH MAHASISWA FAKULTAS HUKUM UNIVERSITAS MALIKUSSALEH, 2022)
In capturing the audience's attention to the advertisements offered, several efforts were made to design attractive advertising content. Starting from the presence of forms of visual communication such as graphic design, branding, billboards/posters and displays in magazines/newspapers, to packaging to produce its own creative visualization in advertising. The first principle of creativity in advertising is that creativity does not create something out of nothing. Creativity in an ad is important to highlight. The goal is of course to attract attention, be different from other advertisements, have good quality and also make it easier to remember and disseminate to the audience. The purpose of this research, besides adding to the scientific repertoire, is also to evaluate and improve the efficiency of advertising. The research method was carried out using literature study methods from various books, journals and reports to find out the definitions and concepts regarding creativity, especially in advertising. The results of the research and the novelty of this study are that not all advertisements are on social media or television, but there are advertisements that use contact points on billboards that must use creativity, originality and visual communication to reach their audience as cigarette products do, besides that The psychology of using color in ad design plays a big role.